Pembuatan Pupuk Organik Cair dari Limbah Pasar dengan Perbandingan Hasil Menggunakan Bioaktifator Air tahu dan EM4 - Anggraini, Lusi; Kuswoyo, Vicky Anderesta; Marsya, Mutia Anissa (Jurnal Jaring SainTek, 2019)
Liquid Fertilizers contain a lot of organic waste which has been decomposed and ready for consumption by plants. By utilizing the remaining vegetables, dried leaves and tofu, it is expected to increase the economic value of waste and reduce environmental pollution. Liquid fertilizer composted by anaerobic fermentation and carried out in a closed bucket (composter) with a comparison of bio-activator wastewater of tofu and EM4. The characterization of liquid fertilizer products was carried out by Nitrogen Analyzer, UV-vis spectroscopies, and AAS tools to test the levels of Nitrogen, Phosphor and Potassium respectively. The Result shown that the N total levels (0,38 %), Phosphor levels (0,06 %), and potassium levels (0,15%) of POC that made from waste water of tofu are higher than POCEM4.